CONTRIBUTION TO THE INTERPRETATION OF THE EROSIVE BEHAVIOR ON THE HILLS OF GUABIRABA, RECIFE – PE, NORTHEASTERN BRAZIL: SEDIMENTOLOGICAL ANALYSIS OF THE SUPERFICIAL STRUTCTURE OF THE LANDSCAPE - Danielle Gomes da Silva; Antonio Carlos de Barros Corrêa; Alexandre de Oliveira Souza; Jefferson Santos; Renata Cavalcante Lamas; Pedro Ricardo da Cunha Nóbrega (Sociedade & Natureza)
The hills of the district of Guabiraba, Recife - PE, show evidences of recent geomorphic disequilibrium as a consequence of an unbalanced erosive budget, mostly attributed to changes in land use. This paper seeks to provide a diagnostic for the recent erosive behavior within this environmental unit of the Municipality of Recife, which overlies the Barreiras Formation sediments, based on the application of a morphostratigraphical approach combined to the sedimentological analysis of recent correlative deposits. Initially, through the usage of remote sensing imagery, a comparison was drawn between two different instants of landscape evolution: 1984 and 2002. The geomorphologic dynamics for that time lapse was assessed by the construction of geomorphic and morphodynamic maps according to Tricart (1977). That procedure has permitted the qualitative evaluation of the erosive behavior for the established timeframe, through the confrontation of spatial arrangements resulting from distinct geomorphic processes. The mapping of process-sensitive geomorphic features was coupled with the description of sedimentological properties of correlative deposits and their sourceareas. This has enabled the characterization of the superficial structure of the landscape. By comparing digital imaging, geomorphic maps and sediment properties, for the time period considered, it was possible to draw the conclusion that the area has evolved towards thestabilization of its morphodynamic units, displaying a sizeable reduction of gullied areas, as a response to the spreading of the “phytoresistatic equilibrium front”, mainly on the hills covered by a second growth anthropicized savanna. Another significant geomorphological change observed, was the elevation of the local base level, on the foot of the widespreadradial gullies by the coalescence of a system of alluvial fans, which are locally dammed and disconnected of the main collecting drainage, by the lanes of an interstate highway. This damming has substantially diminished the erosive energy of the gully system.